2014
DOI: 10.1016/j.jcat.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic interpretation of the effects of acid strength on alkane isomerization turnover rates and selectivity

Abstract: Acid strength effects on alkane isomerization turnover rates and selectivities are probed using hexene isomers as reactants on bifunctional catalysts containing tungsten Keggin polyoxometalates (POM) with different central atoms and exhibiting well-defined structures amenable to reliable estimates of deprotonation energies (DPE) as rigorous descriptors of acid strength. Titrations of protons with hindered bases during catalysis and mechanistic interpretations of rate data on POM acids in terms of a common sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 29 publications
13
99
0
Order By: Relevance
“…Lately, our density functional theory (DFT) calculations showed that the deprotonation energies (DPE) values of Zr─OH on the SZ surface were depended on their surrounding geometry and hydration degree . The DPE values for terminal and bridging Zr─OH groups on a highly dehydrated SZ surface were 1087 and 1206 kJ/mol, which is well in correspondence with the values estimated by lglesia et al (1110‐1165 kJ/mol) . The reported DPE values of hydroxyl on zeolite surface (1170‐1200 kJ/mol) are higher than that of bridging Zr─OH groups, which confirms the presence of superacidic Brønsted sites …”
Section: Activation Of Alkane Over Sulfated Zirconiasupporting
confidence: 86%
See 1 more Smart Citation
“…Lately, our density functional theory (DFT) calculations showed that the deprotonation energies (DPE) values of Zr─OH on the SZ surface were depended on their surrounding geometry and hydration degree . The DPE values for terminal and bridging Zr─OH groups on a highly dehydrated SZ surface were 1087 and 1206 kJ/mol, which is well in correspondence with the values estimated by lglesia et al (1110‐1165 kJ/mol) . The reported DPE values of hydroxyl on zeolite surface (1170‐1200 kJ/mol) are higher than that of bridging Zr─OH groups, which confirms the presence of superacidic Brønsted sites …”
Section: Activation Of Alkane Over Sulfated Zirconiasupporting
confidence: 86%
“…8 The DPE values for terminal and bridging Zr─OH groups on a highly dehydrated SZ surface were 1087 and 1206 kJ/mol, which is well in correspondence with the values estimated by lglesia et al (1110-1165 kJ/mol). [43][44][45][46][47] The reported DPE values of hydroxyl on zeolite surface (1170-1200 kJ/mol) are higher than that of bridging Zr─OH groups, which confirms the presence of superacidic Brønsted sites. 46,48,49 The proposal of above protonation activation pathway is derived from the superacidity of SZ catalyst.…”
Section: Development History Of Activation Pathwaymentioning
confidence: 99%
“…The isomerization (including ring contraction) of alkanes on the Pt/zeolite bifunctional catalyst is generally believed to follow the carbenium ion mechanism: dehydrogenation of alkanes on Pt to olefins, the olefin is then protonated by adjacent BAS forming the carbenium ion, which is rearranged to another olefin through a cyclopropyl carbenium ion transition state followed by the olefin hydrogenation to alkane product . McVicker et al.…”
Section: Discussionmentioning
confidence: 99%
“…This work demonstrates the selective binding of DTBP to Brønsted acids and its inability to bind to Lewis acids. Iglesia and coworkers [42,43] used DTBP as a selective in situ Brønsted acid titrant for n-hexane isomerization over Keggin POMs and 2-butanol dehydration over WO x /ZrO 2 catalysts from 343 to 473 K at ambient pressure. DTBP titrations completely and irreversibly eliminated isomerization and dehydration activity over both of these Brønsted acid catalysts; however, DTBP did not inhibit dehydration of 2-butanol at 403 K over c-Al 2 O 3 , known to possess only Lewis acidity.…”
Section: In Situ Acid Site Identification and Quantification Via 26-mentioning
confidence: 99%